Efek Mediasi Komitmen Organisasional pada Pengaruh Kepercayaan Organisasi terhadap Perilaku Berbagi Pengetahuan - Conchita Valentina Latupapua; Harvey Hiariey; Adolop Larwaku (Universitas Medan Area, 2021)
In the era of advances in science and technology today, knowledge has an important role for organizations. On the other side, many organizations are faced with knowledge management problems. The development of Knowledge Management is currently the concern of many researchers. One of the elements in Knowledge Management that is considered crucial is the knowledge sharing. Ideal practice of knowledge sharing in an organizational environment will have an impact on individuals. Higher education as a knowledge-based organization has an important function in the creation and dissemination of knowledge. Academics tend to cling to knowledge and are reluctant to spread their intellectual resources. This study examines the effects of organizational commitment as mediation to the effect of organisational trust and knowledge sharing behavior. Sample in the research is 52 lecturers of Economy and Business Faculty, Pattimura University. Collected data then analyzed with descriptive and inferential statistics Structure Equation Model using smartLPS 3. The result shows that organizational trust directly affect the knowledge sharing behavior and organizational trust can affects knowledge sharing behavior with mediation of organizational commitment.